IeDEA-WHO Research-Policy Collaboration: contributing real-world evidence to HIV progress reporting and guideline development - Elizabeth Zaniewski; Olga Tymejczyk; Azar Kariminia; Sophie Desmonde; Valériane Leroy; Nathan Ford; Annette H. Sohn; Denis Nash; Marcel Yotebieng; Morna Cornell; Keri N. Althoff; Peter F. Rebeiro; et al. (Elsevier, 2018)
Partnerships between researchers and policymakers can improve uptake and integration of scientific evidence. This article describes the research-policy partnership between the International epidemiology Databases to Evaluate AIDS (IeDEA) (www.iedea.org) and the World Health Organization (WHO), which was established in 2014. IeDEA is an international research consortium, which analyses data on almost 2 million people living with HIV under care in routine settings in 46 countries in Asia-Pacific, the Caribbean, Central and South America, North America and sub-Saharan Africa. Five multiregional analyses were identified to inform the WHO on progress towards the second and third 90s of the 90-90-90 targets in adults and children: (i) trends in CD4 cell counts at the start of antiretroviral therapy (ART); (ii) delays from enrolment in HIV care to ART initiation; (iii) the impact of ART guideline changes; (iv) retention in care, mortality and loss to follow-up; and (v) viral suppression within the first 3 years after initiating ART. Results from these analyses were contributed to the 2015 and 2016 WHO global HIV progress reports, will contribute to the 2018 report, and were published in academic journals. The partnership has been mutually beneficial: discussion of WHO policy agendas led to more policy-framed, relevant and timely IeDEA research, and the collaboration provided the WHO with timely access to the latest data from IeDEA, as it was shared prior to peer-review publication.